Romania Toward a Low Carbon and Climate Resilient Economy : Energy Sector Analysis - World Bank (World Bank, Washington, DC, 2016)
This report is about Energy sector in Romania which is responsible for 58 percent of the country’s GHG emissions (except Land use, land-use change and forestry (LULUCF)), and is therefore critical for mitigation. Romania’s economic growth and energy consumption have been decoupling since the early 1990s, and the energy intensity of the economy has been continuously decreasing, but it is still high. At present, Romanian energy supply system is relatively carbon intensive, but share of zero-carbon energy sources is growing. The energy sector analysis and modeling were designed to find the best solutions for Romania’s energy supply mix given the country’s prospective medium- and long-term climate change mitigation obligations. The key findings were as follows: (i) energy efficiency measures will contain energy demand growth; (ii) as a result of the new investments in the energy sector under the Green and the Super Green scenarios, primary energy supply mix will become cleaner. Under the Baseline scenario; (iii) new investments in the electricity sector will lead to a much cleaner electricity supply mix; (iv) total costs for the energy system are lower under the Green scenario then in the Baseline, but the Super Green mitigation targets require an expense equal to the Baseline one; (v) electricity sector GHG emissions in 2050 are 72 percent and 97 percent below the 2005 level under the Green and Super Green scenarios, respectively; (vi) GHG emission from the energy supply system as a whole would be 25 percent and 50 percent below in 2030 from the 2005 level in the Green and Super green scenarios, respectively; and (vii) Marginal Abatement Cost Curve (MACC) shows that the proposed measures provide a significant potential abatement level totaling in 2050. The conclusions and recommendations were as follows: (a) Romania can meet the GHG mitigation obligations likely under the EU 2030 framework in energy and electricity sectors at moderate costs; (b) The prospective requirements of the EU 2050 Roadmap, which requires at least 80 percent reduction in emissions overall and the virtual elimination of emissions from the power sector, are both expensive and challenging to implement; (c) Implementation of a set of aggressive energy efficiency measures is a key part of the Green and the Super Green scenarios; (d) a lower carbon path for Romania’s energy sector imposes significant costs and complex planning challenges on the sector, in particular on power generation; (e) energy sector in Romania has the potential to become an engine of economic growth; (f) while this assessment included a set of generally-agreed technologies at costs based on today’s best analysis, both technologies and costs will surely evolve, and updated analysis will be needed; and (g) while long-term sector development to 2030 and 2050, the subject of this assessment, is important, the government cannot be distracted from critical near-term sector reforms.